Analisis Faktor-Faktor Penghambat Membaca Permulaan pada Siswa Kelas 1 SD - fitria pramesti (Universitas Pendidikan Ganesha, 2018)
This study aims to analyze inhibiting factors of early reading in grade 1 students of SD Negeri 1 Wonorejo and alternative solutions that can be used to overcome difficulties in reading the beginning. This research method is a type of qualitative research using case study approach. The instruments used were teacher observation sheets, student observation sheets, and interview guidelines. Data collection techniques used are observation, interview, and documentation. Data analysis uses data reduction, data presentation, and conclusions. The results showed that inhibiting factors of reading the beginning on the students of grade 1 SD Negeri 1 Wonorejo are: 1). Intellectual Factors, 2). Environmental factors, 3). Lack of motivation from family side 4). Lack of low student reading interest. While alternative solutions that can be used to overcome difficulties in reading the beginning are: 1). Class teachers prioritize children who have difficulty, 2). The classroom teacher should also pay special attention to children who have difficulty, 3). Good working relationship between classroom teachers and parents 4). Parents should pay more attention, monitor children in learning to read, 5). Students' interests should be developed and trained continuously. The results of this study can be used as an improvement and to improve the quality of learning that can develop interest and ability of low-grade students in reading skills. This research is expected to contribute in the form of thinking for the advancement of ability in reading learning beginning to grade 1 students.